HIV-Associated Multiple Drug Resistant Tuberculosis in a Pregnant Woman: Clinical Course, Treatment Efficacy and Perinatal Outcomes - A. V. Kukurikа; E. I. Yurovskаya; O. V. Serdyuk (Туберкулез и болезни лёгких)
A clinical case of HIV-associated multiple drug resistant tuberculosis in a pregnant woman is presented. The clinical situation was complicated since during the main course of treatment this patient had two pregnancies and delivery with an interval of less than 2 years, and the onset of the disease occurred during the early period in the first pregnancy. This case demonstrates effective treatment of the specific disease and favorable perinatal outcomes. The article assesses medical tactics, analyzes the time of diagnosis, complex therapy, the choice of the way of delivery, considers the need for interdisciplinary interaction at all stages of observation to improve the quality of care.